Sinonimitas Dalam Al-Qur’an: Studi Tentang Lafadz Penciptaan Dalam Al-Qur’an - Agustiar, Agustiar; Mardiah, Mardiah; Suci Febriani, Riska; Pradinata Putra, Vebri; . A, Faizal (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This writing aims to examine the synonyms in the Qur'an, especially in the word creation used in the Muslim holy book. Synonym is the use of words or phrases that have the same or similar meanings in a particular context. Al-Qur'an contains many synonyms in the use of lafadz creation. This synonymy can be seen in several forms, such as perfect synonyms, partial synonyms, similar synonyms, and synonyms with variations in meaning. Perfect synonyms occur when the words used are completely the same in meaning and usage, while partial synonyms occur when only certain parts of the words have the same or similar meanings. In addition, the use of synonyms in the Qur'an gives aesthetic value and beauty in the language used. It can also help enrich the meaning and understanding of creation in the Qur'an. For example, the synonyms of creation between the words "khalaqa" and "sawwara" describe the diversity in the creation of Allah SWT which is seen in the world and the universe. In conclusion, synonyms in the Qur'an show richness and beauty in Arabic and provide enrichment of meaning and understanding of certain themes in the Qur'an